1992
DOI: 10.1093/jnci/84.16.1266
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Prognostic Evaluation of Biological Factors in Primary Breast Cancer

Abstract: Our retrospective analysis has identified protease expression and tumor cell proliferation rate as important biological prognostic factors in breast cancer. Prospective clinical trials should be undertaken to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
44
0
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 0 publications
12
44
0
1
Order By: Relevance
“…Applying completely different uPA ELISAs, these authors reported that a high level of immunoreactive uPA is significantly correlated with high relapse rate and associated with poor prognosis. These observations were later extended and confirmed in other studies [25][26][27]. The uPA ELISA kits employed differed in the type of antibodies used, in the type o f standards and in the instructions on how the tissue extracts had to be prepared.…”
Section: Discussionsupporting
confidence: 64%
“…Applying completely different uPA ELISAs, these authors reported that a high level of immunoreactive uPA is significantly correlated with high relapse rate and associated with poor prognosis. These observations were later extended and confirmed in other studies [25][26][27]. The uPA ELISA kits employed differed in the type of antibodies used, in the type o f standards and in the instructions on how the tissue extracts had to be prepared.…”
Section: Discussionsupporting
confidence: 64%
“…This contrasts with the majority of the larger published studies, in which this correlation was not found for uPA (Foucre et al, 1991;Janicke et al, 1991Janicke et al, , 1993Foekens et al, 1992;Spyratos et al, 1992;Gr0ndahl-Hansen et al, 1993;Bianchi et al, 1994;Bouchet et al, 1994;Gohring et al, 1995) and only partly for PAI-I (Foucre et al, 1991;Janicke et al, 1991Janicke et al, , 1993Gr0ndahl-Hansen et al, 1993;Foekens et al, 1994a).…”
Section: Discussionmentioning
confidence: 72%
“…Although the patients of Spyratos et al (1992) and Bouchet et al (1994) seem similar, the first study included cathepsin D and not PAI-1, while the second study did the opposite. This is no doubt the main explanation for the different results regarding metastasis-free survival (MFS).…”
Section: Discussionmentioning
confidence: 99%
“…Urokinase and its inhibitors have been proposed as new prognostic factors in breast cancer (Duffy et al, 1990;Janicke et al, 1990;Foekens et al, 1992;Spyratos et al, 1992;Bouchet et al 1994;Foekens et al, 1995). However, their use for this purpose can only be envisaged once the results obtained with different assay methods have been compared.…”
Section: Discussionmentioning
confidence: 99%